EDUTAINMENT STRATEGY OF @ROLANSIHOMBING TIKTOK ACCOUNT: BUILDING AUDIENCE ENGAGEMENT THROUGH EDUCATIONAL AND ENTERTAINING CONTENT - Tuty Alawiyah Pulungan; Al-Hafizh Mubarak Hamdan (OPINI: Journal of Communication and Social Science, 2025)
This study analyzes the edutainment strategy used by the TikTok account @rolansihombing_ to build audience engagement through educational running-themed content. The study employed a qualitative approach with content analysis, supported by data collection techniques such as non-participant observation and literature review. The results indicate that the most consistently used primary strategy is personal storytelling combined with humor, demonstrative visualizations, and a delivery style tailored to the characteristics of the TikTok platform. This combination makes technical information such as the concept of "pace" and basic running exercises easier to understand, especially for novice runners, while also increasing engagement in the form of likes, comments, saves, and shares. The findings also align with the Elaboration Likelihood Model (ELM), which emphasizes the influence of emotional engagement in message processing. The study's limitations lie in its focus on a single account and its failure to examine long-term impacts. Further research is recommended to examine longitudinal, cross-platform effects, and audience demographic influences.